Makkunrai Values of Buginese Women: A Literature Approach - Dipoatmodjo, Tenri S. P.; Mustafa, Muh. Yushar; Samba, Jessica E.; Saleh, Muh. Syahraka (Jurnal Riset Bisnis, Manajemen, dan Ilmu Ekonomi, 2024)
This study investigates the makkunrai values held by Buginese women, reflecting their cultural significance and implications for socio-economic dynamics in contemporary society. Makkunrai represents the ideals of femininity among the Buginese people, emphasising qualities such as perseverance, resilience, and a spirit of adaptability. This literature review synthesises existing scholarship, exploring the historical, sociological, and anthropological dimensions of these values. The research highlights how these values shape the identity and roles of Buginese women in both familial and communal contexts, supporting their position in traditional and modern settings. Crucially, the study examines the impact of modernisation, globalisation, and cultural fluctuations on these values, revealing both continuity and change. By contextualising the challenges that contemporary Buginese women face, including educational access, economic opportunities, and societal expectations, the findings offer insights into how makkunrai values are negotiated and redefined. This literature approach not only enriches the understanding of Buginese women’s cultural heritage but also underscores the importance of preserving traditional values amidst evolving societal dynamics. The study calls for further interdisciplinary research to explore the implications of these values for gender equity and empowerment in Indonesia. Penelitian ini mengkaji nilai-nilai makkunrai yang dianut oleh perempuan Bugis, mencerminkan signifikansi budaya dan implikasinya terhadap dinamika sosial-ekonomi dalam masyarakat kontemporer. Makkunrai mewakili ideal femininitas di kalangan masyarakat Bugis, menekankan kualitas seperti ketekunan, ketahanan, dan semangat adaptasi. Tinjauan literatur ini menyintesis karya-karya akademik yang ada, mengeksplorasi dimensi historis, sosiologis, dan antropologis dari nilai-nilai tersebut. Penelitian ini menyoroti bagaimana nilai-nilai ini membentuk identitas dan peran perempuan Bugis dalam konteks keluarga dan komunitas, mendukung posisi mereka dalam lingkungan tradisional maupun modern. Secara krusial, studi ini menganalisis dampak modernisasi, globalisasi, dan fluktuasi budaya terhadap nilai-nilai tersebut, mengungkapkan baik kontinuitas maupun perubahan. Dengan melakukan pendekatan kontekstual terhadap tantangan yang dihadapi perempuan Bugis kontemporer, termasuk akses pendidikan, peluang ekonomi, dan ekspektasi sosial, temuan ini memberikan wawasan tentang bagaimana nilai-nilai makkunrai dinegosiasikan dan didefinisikan ulang. Pendekatan literatur ini tidak hanya memperkaya pemahaman tentang warisan budaya perempuan Bugis tetapi juga menekankan pentingnya menjaga nilai-nilai tradisional di tengah dinamika sosial yang terus berkembang. Studi ini menyerukan penelitian interdisiplin lebih lanjut untuk mengeksplorasi implikasi nilai-nilai ini bagi kesetaraan gender dan pemberdayaan di Indonesia.